2014
DOI: 10.1371/journal.pone.0097647
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Kisspeptin during Mouse Decidualization

Abstract: BackgroundPlasma kisspeptin levels dramatically increased during the first trimester of human pregnancy, which is similar to pregnancy specific glycoprotein-human chorionic gonadotropin. However, its particular role in the implantation and decidualization has not been fully unraveled. Here, the study was conducted to investigate the expression and function of kisspeptin in mouse uterus during early pregnancy and decidualization.Methodology/Principal FindingsQuantitative PCR results demonstrated that Kiss1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 32 publications
4
51
1
3
Order By: Relevance
“…Additionally, because exogenous gonadotropins, E 2 and progesterone could not rescue the implantation failure, we concluded that the defect was uterine based (Calder et al 2014) and considered that it was the lack of a functional uterine-based kisspeptin signaling system in the null female that disrupted embryo implantation. In support of this idea, we found that on the day of implantation (D4 of pregnancy), the WT mouse uterus expresses kisspeptin and Kiss1r, a finding also made by Zhang et al (2014) based on both RT-PCR and immunohistochemical analyses. More importantly, we also demonstrated that at this critical peri-implantation period, the WT uterus expresses a functional kisspeptin/ KISS1R signaling system localized to both the luminal and glandular epithelia (Fig.…”
Section: Kisspeptin Positively Regulates Embryo Implantationsupporting
confidence: 67%
See 1 more Smart Citation
“…Additionally, because exogenous gonadotropins, E 2 and progesterone could not rescue the implantation failure, we concluded that the defect was uterine based (Calder et al 2014) and considered that it was the lack of a functional uterine-based kisspeptin signaling system in the null female that disrupted embryo implantation. In support of this idea, we found that on the day of implantation (D4 of pregnancy), the WT mouse uterus expresses kisspeptin and Kiss1r, a finding also made by Zhang et al (2014) based on both RT-PCR and immunohistochemical analyses. More importantly, we also demonstrated that at this critical peri-implantation period, the WT uterus expresses a functional kisspeptin/ KISS1R signaling system localized to both the luminal and glandular epithelia (Fig.…”
Section: Kisspeptin Positively Regulates Embryo Implantationsupporting
confidence: 67%
“…However, Zhang et al (2014) found that the expression of Kiss1 and Kiss1r in the mouse uterus was not transiently restricted to the periimplantation period. Instead, they found that between D5 and D8 the expression of these molecules increased significantly in the pseudopregnant uterus during artificially induced decidualization.…”
Section: Kiss1mentioning
confidence: 93%
“…Although the process of decidualisation is different in humans, occurring before implantation in contrast to the post-implantation process occurring in rodents (Zhang et al 2014), the findings suggested a possible mechanism underlying the relationship between kisspeptin and placental function. Evidence has also demonstrated that not only does Kiss1 and Kiss1r mRNA expression increase, but that in rodents during implantation, a functional kisspeptin signalling system exists.…”
Section: Implantation and Placental Functionmentioning
confidence: 88%
“…Zhang and coworkers reported uterine expression of Kiss1 and Kiss1r mRNA was significantly greater with decidualisation (P < 0.01) (Zhang et al 2014). Interestingly, this was also observed in pseudopregnancy, suggesting a process independent of the developing embryo.…”
Section: Implantation and Placental Functionmentioning
confidence: 90%
“…It was explained further that localised uterine kisspeptin signalling modulates embryo implantation by regulating localised leukocyte inhibitory factor (LIF) secretion, which has been shown to be critical for implantation in mice [162,163]. Similarly, studies in mice have shown increased expression of kiss1 and kiss1r at the time of endometrial decidualisation, and the process was attenuated by downregulating kiss1 expression [164].…”
Section: Prace Poglądowementioning
confidence: 99%